Desafios da adesão à dieta sem glúten - OLIVEIRA, Dafne Cristine Lima de (2023)
The glutenfree diet is a strategy widely used as a treatment for various diseases. However, it is a very restrictive diet, which makes adherence challenging. Thus, low adherence is common even among celiac patients, whose only form of treatment is following this diet, and several factors are stated as the cause for this behavior. Therefore, this study aims to discuss several factors that can impair adherence to a glutenfree diet. In this regard, bibliographic research was carried out from June to December 2021, with references from the last five years, from the academic databases Scielo, Pubmed, Science.gov, Scopus, and Google Scholar. Hence, this work is presented in the form of a scientific article, carried out according to the norms of the journal where it was published: Research, Society and Development. According to the bibliography consulted, the challenges of adherence to a glutenfree diet have different origins and are often difficult to solve. Questions such as consumer knowledge about the gluten free diet and food labels are crucial for adherence, just like the adequacy of the labels and expertise on the part of food handlers. Furthermore, glutenfree products were extensively addressed in the articles due to issues such as high cost, low availability, and accessibility, in addition to the risks of crosscontamination and sensory characteristics that are not always pleasant. Finally, it should be noted that several social and individual aspects such as age, sex, education, and mental health are involved in adherence to a glutenfree diet. In light of this, it is evident that the factors that interfere with adherence are diverse, and the need for individualized and detailed care is highlighted as the main means of monitoring adherence to the diet so that assertive interventions can be applied. Moreover, further studies should focus on interventions, and thus improve the autonomy of people who must follow a glutenfree diet, minimize the impact of social situations and even improve products and establishments.